ChemInform Abstract: Hirsutellones and Beyond: Figuring Out the Biological and Synthetic Logics Toward Chemical Complexity in Fungal PKS‐NRPS Compounds. Issue 29 (1st July 2013) - Li, Xu‐Wen; Ear, Alexandre; Nay, Bastien
Abstract: Review: 115 refs.